MENGKREASI TEKS DRAMA(TIK) MELALUI KONSEPSI LAJOS EGRI: PERSOALAN TEORI, METODE DAN EVALUASI - Purwanto Lephen (Institut Seni Indonesia Yogyakarta, 2025)
Research on the creation of drama(tic) texts still leaves issues of theory, method and evaluation of early works (prototypes) before the work is published. One of the most commonly used theories is that of Lajos Egri. Lajos Egri has not mentioned the source of drama text creation, the methods used, and the evaluation that must be done in order to become a quality drama work. The study method used relates to empirical experience, observation and literature review of research-based drama text creation. As a result, the theory of drama text creation (Lajos Egri) can be used by adding creation sources, creation methods, evaluation of initial creation, stabilising the quality of the work with a certain structure or aesthetic, and publication of the work. Further research can be conducted on modifying Lajos Egri's theory for the creation of visual theatre, body theatre, musical theatre and audio theatre texts.